Do Takeover Targets Overinvest? - Servaes, H. (Review of Financial Studies, 1994)
I examine the capital expenditures of a sample of 700 takeover targets and firms that went private over the period 1972–1987. For the complete sample, I do not find evidence that takeover targets increase their capital expenditures over the four-year period before the acquisition or that they overinvest in capital expenditures relative to several benchmarks. Subsample results provide some evidence of overinvestment in oil and gas firms and large firms. There is no evidence of overinvestment, however, for firms acquired in a hostile takeover or firms that went private. In general, these results are not consistent with the conjecture that takeovers are motivated by the need to reduce excess investment in capital expenditures in target firms.